Interrelationship between energy efficiency and spectral efficiency in cognitive femtocell networks: A survey - Ghosh, Joydev (Pervasive and mobile computing, 2019)
In this paper, initially the issues of spectrum allocation among macro (or “licensed”) and Femto (or “unlicensed”) users in an Orthogonal Frequency Division Multiple Access (OFDMA) based dual-layer femtocell networks have dealt with. This research contribution leads to basic coin in the design of next generation (5G) wireless networks. This manuscript exemplifies the trade-off issues of energy efficiency (EE) and spectral efficiency (SE) with both cooperative and non-cooperative architecture in cognitive femtocell networks. The pivotal concepts for each technology are described along with their potential impact on 5G and the research challenges that remain. Further, the trade-off between EE and SE is reposed with respect to the state of the art. The obtained insightful observations from the trade-off analysis of EE ans SE can lead to provide design guideline for 5G wireless Networks.